Fatigue Failure Stages of VT1-0 Titanium in Different Structural States. Study by Acoustic Emission Method - Bashkov O. V.; Sharkeev Yu. P. Yury Petrovich; Panin S. V. Sergey Viktorovich; Kim V. А.; Bashkova Т. I.; Popkova А. А.; Eroshenko А. Yu.; Tolmachev А. I. (2016, 2016)
Title screen